Destination repurposed: transformative impacts of refugee crisis. Issue 2 (4th March 2022) - Hoque, Md Ariful; Faisal, Abrar; Shoeb-Ur-Rahman, Muhammad
ABSTRACT: This research note generates insights into the transformational impacts of the refugee crisis and finds that the influx of aid workers significantly alters the business landscapes and destination image of a tourism-dependent urban area. The study draws on qualitative semi-structured interviews and an extensive analysis of policy documents, organisational reports and news articles pertaining to the responses to the impacts of the world's largest refugee settlement in Cox's Bazar, Bangladesh. The empirical evidence identifies how a tourism-dependent visitor economy transformed into the current state of aid worker-led economy. In so doing, the study explores significant knowledge gaps in the tourism literature and suggests future research to address the refugee crisis-tourism nexus in a context of the host community.